AmMYB24 Regulates Floral Terpenoid Biosynthesis Induced by Blue Light in Snapdragon Flowers - Han, Jianing; Li, Tong; Wang, Xuelian; Zhang, Xi; Bai, Xiaoning; Shao, Huihui; Wang, Shaojie; Hu, Zenghui; Wu, Jing; Leng, Pingsheng (Frontiers in Plant Science, 2022)
Floral terpenoid volatiles are impacted by light quality. In snapdragon, blue light can significantly enhance the emissions of ocimene and myrcene and the expression of ocimene synthase (AmOCS) and myrcene synthase (AmMYS). However, the mechanisms underlying to the response to blue light are largely unknown. In this study, two transcription factors, AmMYB24 and AmMYB63 were screened which showed high expression level under blue light. AmMYB24 exhibited synchronous expression with AmOCS and activated its expression significantly when overexpressed and under blue light treatment. This activation is direct and occurs through binding of AmMYB24 to MYBCORECYCATB1 sites in the AmOCS promoter. In addition, AmMYB24 interacts with the blue light signal key receptor AmCRY1 and the transcriptional activation activity of AmMYB24 was decreased in AmCRY1 silencing flowers. Taken together, our results revealed the regulatory pathway of biosynthesis of ocimene induced by blue light mediated by AmMYB24 and AmCRY1. When snapdragon flowers were exposed to blue light, AmCRY1 was first activated, the light signal is transduced to AmMYB24 through interaction with AmCRY1, and finally AmMYB24 activates AmOCS by binding to its MYBCOREATCYCB1 motif, resulting in abundant ocimene emission.